VOCABULARY DEVELOPMENT (Ustozlar uchun, 2026)
Vocabulary development plays a critical role in the process of language acquisition and academic achievement. As individuals grow from childhood to adulthood, the expansion of vocabulary is not only crucial for effective communication but also for cognitive growth, comprehension skills, and social development. A rich and diverse vocabulary allows individuals to express thoughts, emotions, and experiences with greater clarity and precision. It facilitates deeper understanding of texts, enhances writing abilities, and supports overall academic success.